2021
DOI: 10.3389/fcell.2021.734818
|View full text |Cite
|
Sign up to set email alerts
|

TEOA Promotes Autophagic Cell Death via ROS-Mediated Inhibition of mTOR/p70S6k Signaling Pathway in Pancreatic Cancer Cells

Abstract: Pancreatic cancer is a common malignant tumor with high mortality, and novel therapeutic options have focused on ameliorating its poor prognosis. TEOA, a traditional Chinese herbal medicine, exhibits anti-inflammatory and anti-cancer activities. Our recent study has shown that TEOA inhibits proliferation and induces DNA damage in diffuse large B-cell lymphoma cells by activating the ROS-mediated p38 MAPK pathway. However, its effects on pancreatic cancer cells remain unknown. In the present study, we evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…The clonogenic ability of cells was carried out according to our previous published paper [ 24 ]. The cells were collected and seeded on a 12-well plate with a density of 2,000 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…The clonogenic ability of cells was carried out according to our previous published paper [ 24 ]. The cells were collected and seeded on a 12-well plate with a density of 2,000 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Yang et al demonstrated that this herbal inhibited the proliferation and migration of PC cells concurrently, causing the induction of mitochondrial dysfunction in PANC1 and SW1990 cells. Finally, TEOA induced autophagic cell death in PC cells by inactivating the ROS-dependent mTOR/p70S6k signaling pathway [168].…”
Section: Sugiolmentioning
confidence: 96%
“…Additionally, autophagy is increasingly investigated as a molecular target for cancer therapy. Our recent study demonstrated that excess autophagy results in autophagic cell death ( 12 ). However, autophagy plays two roles in tumorigenesis and development.…”
Section: Introductionmentioning
confidence: 99%